1995
DOI: 10.1007/bf02211800
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of progesterone vaginal suppositories in alleviation of nervous symptoms in patients with premenstrual syndrome

Abstract: Metabolites of progesterone (pregnanolone and allopregnanolone) may play a physiologic role as anxiolytic agents, perhaps modifying mood and anxiety; the current study confirms the utility of twice daily, 200-mg progesterone vaginal suppositories, in the alleviation of some PMS symptoms relating to anxiety and irritability. Further evaluation may be warranted to ascertain which patients in the known heterogeneous PMS population may be most likely to benefit from such treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Figure 1 shows the individual standardised mean difference for each trial, the type of preparation and dosage for that trial, and the pooled standardised mean difference with 95% confidence intervals for trials that used progesterone suppositories and those that used oral micronised progesterone. The inclusion of the data from the two low quality trials 25 26 did not significantly affect the overall result.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure 1 shows the individual standardised mean difference for each trial, the type of preparation and dosage for that trial, and the pooled standardised mean difference with 95% confidence intervals for trials that used progesterone suppositories and those that used oral micronised progesterone. The inclusion of the data from the two low quality trials 25 26 did not significantly affect the overall result.…”
Section: Resultsmentioning
confidence: 94%
“…We excluded four: two because of their low quality score on the Jadad scale, 26 27 one because the data could not be extracted,29 and one because the trial failed to make a prospective diagnosis of premenstrual syndrome before randomisation 24. Ten trials remained, representing 531 women with data suitable for inclusion in the analyses.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several studies focussed on the putative beneficial effects of progesterone administration in patients suffering from premenstrual syndrome (PMS), which in part overlaps with depressive symptomatology. While some investigations reported an improvement of mood (Baker et al 1995;Dennerstein et al 1980;Magill 1995) in women suffering from PMS, others found no superiority to placebo treatment (Freeman et al 1990(Freeman et al , 1995Vanselow et al 1996). Moreover, no correlation between progesterone levels (Hsiao et al 2004;Schmidt et al 1994) and clinical symptoms of PMS have been detected so far.…”
Section: Progesterone In Depression and Anxiety Disordersmentioning
confidence: 99%
“…In addition, several studies focused on the putative beneficial effects of progesterone administration in patients suffering from PMS, which in part overlaps with depressive symptomatology. While some investigations reported an improvement in mood [67,68,69] in women suffering from PMS, others found no superiority to placebo treatment [70,71,72]. Furthermore, the previously recommended prophylactic postpartum use of progesterone in women who had experienced postpartum depression in the past [73] was challenged by an observed enhanced risk of postpartum depression after progesterone therapy [74].…”
Section: Therapeutic Potential Of Neuroactive Steroids In the Treatmementioning
confidence: 99%